How Can Implementers Apply Digital Personalised Learning in Schools? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at digital personalised learning (DPL), a promising EdTech approach to improving learning outcomes, and consider how to implement this approach in school settings. We draw on work from EdTech Hub and other prominent researchers to first unpack the ‘basics’ of DPL implementation. These include the importance of teaching at the right level as a driver of DPL’s impact, and how DPL tools are applied in schools as supplementary learning and / or integrated into existing curricula. We also consider some of DPL’s technical requirements and achievements in improving learning outcomes. We then explore emerging insights about effective DPL implementation in schools, including the role of teachers as facilitators, the evidence behind student-device ratios, and the importance of coordinating DPL implementation with broader education system actors. Lastly, we look at areas that require further research, noting issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to DPL application in education systems. Keywords: digital personalised learning; DPL; implementation research; teaching at the right level; learning outcomes; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10616734 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1008 ZenodoArchiveConcept: 10616733
Keywords: _r:AddedByMyEducationEvidence

What Should Ministries of Education Prioritise When Crafting Their Edtech Strategies? - Thinley, Sangay (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at priorities for governments and ministries of education when crafting EdTech Strategies. Interest in developing EdTech strategies related to operational targets and outcomes has increased over the past few years, especially in response to the learning disruptions caused by the Covid-19 pandemic. Evidence suggests that countries with established EdTech strategies were better equipped to respond to the pandemic and its effects due to their advanced preparation and readiness for large-scale remote learning. We examine the key principles for EdTech strategies, including the importance of focusing on learning outcomes, inclusivity, teacher training, costs, and contextual needs, among other factors. We draw on EdTech Hub's work in supporting several governments in designing and implementing EdTech strategies, as well as broader evidence from the field, to offer practical insights. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt, such as prioritising consultative processes of strategy development while focusing on multi-modal, problem-driven EdTech solutions and interventions guided by a unifying educational goal. We highlight areas that require further research, in particular questions related to cost-effective approaches to improving global learning, how governments can develop dynamic and iterative strategies, and the role of private sector partnerships in the successful implementation of EdTech strategies. Keywords: EdTech; education technology; education strategy; best practices for EdTech; EdTech planning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13360175 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1054 ZenodoArchiveConcept: 13360174
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10987889 ZenodoArchiveConcept: 10987888 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1006 10.53832/edtechhub.1023 2339240:U7UE5PIN 2405685:B422KBGQ 2405685:HD58IXI3 2405685:PGRMI8NH
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10610797 ZenodoArchiveConcept: 10610796 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1007 2339240:SZE9FBW4 2405685:IIAMD77T
Keywords: _r:AddedByMyEducationEvidence

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7783382 ZenodoArchiveConcept: 7783381 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7783382 10.53832/edtechhub.0167 2339240:R9JRWMKC 2405685:6CC8GQZP 2405685:XHJC3W67
Keywords: _r:AddedByZotZen